Educational Values in the Al-Qur'an: Tarbawi Interpretation's Perspective on the Formation of Students' Character - Yeti Dewanti; Wiwit Akriani; Ani Maghfiroh (Journal of Innovative and Creativity, 2026)
This study examines the educational values embedded in the Qur’an through the perspective of Tafsir Tarbawi and their relevance to character formation in contemporary education. Employing a qualitative research design with a library research approach, the study analyzes selected Qur’anic verses, classical and contemporary Qur’anic commentaries, and recent scholarly works on Islamic education published between 2020 and 2025. The findings reveal that the Qur’an contains comprehensive educational principles that integrate cognitive development, moral cultivation, and spiritual awareness. Through Tafsir Tarbawi, these values are interpreted as a holistic educational framework that emphasizes knowledge acquisition grounded in divine consciousness, the internalization of moral values, and the role of educators as moral exemplars. The study also highlights the relevance of Tafsir Tarbawi in addressing the character crisis faced by modern educational systems, characterized by moral degradation and value disorientation. Despite challenges related to institutional support and teacher competence, Tafsir Tarbawi offers a normative and contextual foundation for Qur’an-based character education. This research contributes to Islamic educational discourse by positioning Tafsir Tarbawi as an integrative approach that bridges Qur’anic revelation and contemporary educational practice.